2013
DOI: 10.1007/s10661-013-3251-y
|View full text |Cite
|
Sign up to set email alerts
|

DDT, DDE, and 1-hydroxypyrene levels in children (in blood and urine samples) from Chiapas and Oaxaca, Mexico

Abstract: The aim of this study was to evaluate the DDT, DDE, and 1-hydroxypyrene exposure levels of children living in communities located in southeastern Mexico. The study communities were Lacanja and Victoria in Chiapas state and Ventanilla in Oaxaca state. Children living in Lacanja had total blood DDT levels (mean ± SD, 29,039.6 ± 11,261.4 ng/g lipid) that were significantly higher than those of children in Victoria (10,220.5 ± 7,893.1 ng/g lipid) and Ventanilla (11,659.7 ± 6,683.7 ng/g lipid). With respect to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Data obtained in this investigation showed that the highest mean urinary 1‐OHP level was detected in women who use wood as their principal indoor fuel source for cooking and heating (0.55 ± 0.52 μmol/mol creatinine) (Table ). In line with our results, high urinary 1‐OHP levels have been detected in people chronically exposed to biomass smoke in different studies performed in Mexico (Martínez‐Salinas et al, ; Riojas‐Rodriguez et al, ; Martínez‐salinas et al, ; Pruneda‐Álvarez et al, ; Trejo‐Acevedo et al, , ; Jasso‐Pineda et al, ; Ruiz‐Vera et al, ). Besides, it has been demonstrated that urinary 1‐OHP levels in populations that use biomass combustion as an indoor fuel source is generally higher than those urinary 1‐OHP concentrations found in populations exposed to PAHs through other exposure sources such as vehicular traffic, occupational settings, industrial areas, among others (Chetiyanukornkul et al, ; Polanska et al, ; Yuan et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Data obtained in this investigation showed that the highest mean urinary 1‐OHP level was detected in women who use wood as their principal indoor fuel source for cooking and heating (0.55 ± 0.52 μmol/mol creatinine) (Table ). In line with our results, high urinary 1‐OHP levels have been detected in people chronically exposed to biomass smoke in different studies performed in Mexico (Martínez‐Salinas et al, ; Riojas‐Rodriguez et al, ; Martínez‐salinas et al, ; Pruneda‐Álvarez et al, ; Trejo‐Acevedo et al, , ; Jasso‐Pineda et al, ; Ruiz‐Vera et al, ). Besides, it has been demonstrated that urinary 1‐OHP levels in populations that use biomass combustion as an indoor fuel source is generally higher than those urinary 1‐OHP concentrations found in populations exposed to PAHs through other exposure sources such as vehicular traffic, occupational settings, industrial areas, among others (Chetiyanukornkul et al, ; Polanska et al, ; Yuan et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Dichlorodiphenyltrichloroethane (DDT), one of the typical persistent organic pollutants, was used worldwide in agricultural pest control and vector-borne disease control. Although the use of DDT has been limited internationally, its presence in unchanged or modified forms is still observed in the environment (water, sediment, and soil) (Dai et al, 2014, Turgut et al, 2013, Tang et al, 2014, Veljanoska-sarafiloska et al, 2013) and can even be detected in fodder plants (Yehouenou et al, 2013) in the bodies of animals (Deribe et al, 2013) and humans (Pérez-Maldonado et al, 2013, Teeyapant et al, 2014). This finding is attributed to its persistence, bioaccumulation, toxicity, and physical–chemical capacity for long-range transport (Aneck-Hahn et al, 2007, Sadasivaiah et al, 2007, Skinner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Yáñez et al [ 13 ] reported that the breast milk from women living in Chiapas had higher levels of DDT and its main metabolite dichlorodiphenyldichloroethylene (DDE) than breast-feeding women from other states, including Oaxaca, Quintana Roo, and San Luis Potosi. Other studies have reported high levels of DDT and its metabolites in blood of children [ 3 , 4 , 14 , 15 ]. Notably, children in Chiapas had the highest levels of DDT and its metabolites out of all children participating in a study that covered several communities of Mesoamerican countries [ 3 ].…”
Section: Introductionmentioning
confidence: 99%